Differences in Lipid Profiles and Atherogenic Indices Between Hypertensive and Normotensive Populations: A Cross-Sectional Study of 11 Chinese Cities - Cheng, Wenke; Wang, Lili; Chen, Siwei (Frontiers in Cardiovascular Medicine, 2022)
Background: Several previous studies have reported that dyslipidemia is associated with the risk of hypertension, but these studies are mainly conducted in the European and US populations, with few studies in the Asian population. Moreover, the effects of atherosclerotic indices including atherogenic coefficient (AC) and atherogenic risk of plasma (AIP) on hypertension in Asians have not been well described. Methods: From 2010 to 2016, altogether 211,833 Chinese adults were ultimately recruited at the health centers in 11 Chinese cities. Differences in continuous variables between two groups were analyzed by the Man-Whitney test, while those in categorical variables were examined by the Chi-square test. Logistic regression was applied to evaluate the association between lipid profiles and the risk of hypertension. The predictive values of AC and AIP for the incidence of hypertension were analyzed by the area under the receiver operating characteristic (ROC) curve. Meanwhile, Bayesian network (BN) models were performed to further analyze the associations between different covariates and the incidence of hypertension. Results: A total of 117,056 participants were included in the final analysis. There were significant differences in baseline characteristics between normotension and hypertension groups (p<0.001). In multivariate logistic regression, the risk of hypertension increased by 0.2% (1.002 [1.001-1.003]), 0.2% (1.002 [1.001-1.003]), and 0.2% (1.002 [1.001-1.003]) per 1 mg/dl increase in total cholesterol (TC), low-density lipoprotein (LDL), and non-high-density lipoprotein cholesterol (non-HDL-c), respectively. However, after adjusting for BMI, an increase in HDL level was associated with a higher risk of hypertension (p for trend < 0.001), and the risk of hypertension increased by 0.6% per 1 mg/dl increase in HDL-c (1.006 [1.003-1.008]). In females, AC had the highest predictive value for the incidence of hypertension with an area under the curve (AUC) of 0.667 [95% confidence interval (CI): 0.659-0.674]. BN models suggested TC and LDL was more closely related to the incidence of hypertension. Conclusions: Overall, the lipid profiles were significantly abnormal in the hypertensive population compared to the normotensive population. TC and LDL were strongly associated with the incidence of hypertension. In addition, AC has a good predictive value for the incidence of hypertension in females.